Development of Learning Media of Metal Casting Sand Casting Method Based on Virtual Laboratory for Increase Creative Skill - Purnomo, Purnomo (BRILIANT: Jurnal Riset dan Konseptual, 2023)
Practical learning at Vocational High Schools (SMK) before the Covid-19 pandemic has left a problem, namely a lack of competence. In particular, in the metal casting practicum using the sand casting method, students still have many difficulties in recognizing and using the tools and materials found in the laboratory. This study aims to develop learning media for metal casting using the virtual laboratory-based sand casting method. The development model used is the waterfall software development model. The steps contained in the development of this model consist of (1) analysis of material requirements, practical equipment, occupational safety and health equipment and users; (2) product design in accordance with the results of the previous analysis; (3) Coding of the developed learning media. This coding requires Unity 3D software. Last is (4) testing